ECONOMIC LOSSES CAUSED BY ROSE BEETLE MALADERA INSANABILIS (BRENSKE) ON FRUIT AND ORNAMENTAL PLANTS AND ITS CONTROL BY PATHOGENIC FUNGI: ECONOMIC LOSSES CAUSED BY ROSE BEETLE MALADERA INSANABILIS (BRENSKE) ON FRUIT AND ORNAMENTAL PLANTS AND ITS CONTROL BY PATHOGENIC FUNGI (Iraqi Journal of Market Research and Consumer Protection, 2019)
The study aimed to evaluate injuries and economic losses which caused by rose beetle Maladerainsanabilis (Brenske) on ornamental and fruit plants as introduced insect in Iraq during 2015 and determine infested host plants in addition to evaluate efficacy of pathogenic fungi Metarhiziumanisopiliae (1x10⁹ spore/ ml) and Beauvariabassiana (1x10⁸spore/ ml) in mortality of insect larvae in laboratory and field.The results showed that the insect was polyphagous infested many host plants (20 host plant)Which caused degradation and dead the plants through adult feeding on leaves and flower but large injury caused by larvae feeding on root plants which caused obligate dead to infested plant, the percentage mortality of rose plants 68.6%, pear 45% lantana camare 18.3%, apricot 15.1 and zizphus 1.7% during October 2016. Due to the number of larvae present around root plant, the insect preferred rose and pear plant which recorded high numbers of larvae compared the lowest number of larvae on ziziphus which least preferred. The results were confirmed that the employment of the Metarhiziumanisoplae and Beauveriabassiana formulation in the field to treatment the soil were not effective to causing mortality of the larvae because of the very high temperature during the experiments time. Although, using the same fungi in the laboratory afford efficiency when the formulations were sprayed directly on the larvae or on the soil. The directly treatments with B. bassianaand M. anisoplae were achieved very high mortality reached 100% after 32 and 42 day respectively. While when the formulations were sprayed on the soil the mortality was reached 100% after 63 day for both fungus.